Probe formation in proton beam writing facility at IAP NASU - Lapin, O.S.; Ponomarev, A.G. (Вопросы атомной науки и техники, 2015)
The principles of a proton beam writing facility were described. Particular attention was paid to the problem of probe-forming system design. It was shown that using of separate systems and parts of the scanning nuclear microprobe is the most effective solution. Various probe-forming system configurations for proton beam writing facility have been investigated. The optimization problem of proton beam formation was solved. On the base of this solution the probe-forming system which has best corresponded to requirements for the lithographic process has been found.